2011
DOI: 10.1128/jb.00059-11
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Guided Investigation of Lipopolysaccharide O-Antigen Chain Length Regulators Reveals Regions Critical for Modal Length Control

Abstract: We also showed that there is no synergy between these regions. In particular, region 269 to 274 also influenced chain length distribution mediated by two distantly related PCPs, WzzB and FepE. Furthermore, from the 3 regions uncovered in this study, region 269 to 274 appeared to be critical for the stability of the oligomeric form of Wzz, as determined by cross-linking experiments. Together, our data suggest that chain length determination depends on regions that likely contribute to stabilize a supramolecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 39 publications
5
47
0
Order By: Relevance
“…3 and Table 2), suggesting that maintenance of the negative charge at this position is critical. This correlates with data by Kalynych et al (2011), whereby substitution or deletion of the FepE amino acid region 256-273 (where D268 is located) resulted in shortened LPS Oag chain lengths. We report for the first time two specific residues, L168 and D268, which are essential for FepE function in LPS Oag modal chain length determination.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…3 and Table 2), suggesting that maintenance of the negative charge at this position is critical. This correlates with data by Kalynych et al (2011), whereby substitution or deletion of the FepE amino acid region 256-273 (where D268 is located) resulted in shortened LPS Oag chain lengths. We report for the first time two specific residues, L168 and D268, which are essential for FepE function in LPS Oag modal chain length determination.…”
Section: Discussionsupporting
confidence: 75%
“…Notably, two of these positions, D268 and G274, are located in the FepE region spanning amino acid residues 240-299 which correlates to the WzzB SF segment spanning residues 200-255 based on sequence alignment (Tocilj et al, 2008). Kalynych et al (2011) showed that this functionally important WzzB SF segment was predominantly located on the external surface of the WzzB SF oligomer and hypothesized that the external surface of chain length regulators might represent the principal site of modal length control. Residues D268 and G274 located within this same region of FepE, however, point towards the internal cavity of the oligomer and still affect LPS Oag modal chain length (Figs 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations